Implementasi Pengembangan Koleksi di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Dhia, Fairuz Syauqi; Erlianti, Gustina (Al-DYAS, 2024)
This research examines the implementation of collection development at the West Sumatra Province Archives and Library Service in an effort to fulfill the information needs of users. Libraries play an important role in preserving knowledge and culture, therefore, a clear collection development policy that involves all relevant parties is very necessary. The research uses descriptive methods to provide a detailed picture of the process and challenges in collection development.The research results show that library needs analysis is carried out regularly through surveys to ensure collections cover various age groups and information needs. Library material selection policies are influenced by the budget prepared by the government and additional sources such as grants. Selection of library materials is carried out annually based on a survey of library needs with references from publisher catalogues, the internet and reviews. The procurement process involves the stages of selection, purchasing and processing of library materials using the Inlislite system. Weeding is carried out to maintain the relevance and quality of the collection, although limited funds are an obstacle in this process. Collection eval_uation is carried out to ensure the relevance and physical condition of library materials.In conclusion, library collection development must consider budget, user needs, and relevance of information to ensure the collection remains high quality and useful. The main challenges faced include a lack of collaboration between librarians and users, funding uncertainty, and a lack of supporting facilities and infrastructure.